HARD-MODE INFRARED SPECTROSCOPY OF PEROVSKITES ACROSS THE CATIO3-SRTIO3 SOLID SOLUTION - Meyer H.-W.; Carpenter M.A.; Becerro A.I.; Seifert F. (My University, 2002)
Powder infrared spectra of perovskites across the CaTiO3-SrTiO3 solid solution have been collected at room temperature for the range 20–700 cm−1. Frequency, intensity, and line broadening parameters vary with a pattern that appears to follow the development of the orthorhombic shear strain for the Pnma structure. The data are at least consistent with the Pm3m ↔ I4/mcm transition at Sr-rich compositions being continuous in character and the tetragonal ↔ orthorhombic transition at ~62% SrTiO3 content being discontinuous. In spite of the fact that crystals with intermediate composition have recently been shown to have Pnma rather than Cmcm symmetry, autocorrelation analysis of their IR spectra shows that they have features which distinguish them from crystals with Pnma symmetry for CaTiO3 rich compositions. In particular, crystals of intermediate composition have the highest values of the line broadening parameter, Δcorr, for the solid solution, suggesting that they are characterized by relatively high degrees of local structural heterogeneity.